1997
DOI: 10.3147/jsfp.32.193
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Elevated Water Temperature Treatment of Ayu Infected with the Microsporidian Glugea plecoglossi.

Abstract: Preliminary experiments showed that treatment of Glugea-infected ayu at an elevated water temperature of 27-29•Ž was effective in controlling the disease. Attempts were made to determine the optimal timing of the treatment and to compare the efficacy of single and double treatments (performed once or twice), after infecting fish by feeding fresh spores of G. plecoglossi. In Experiment 1, fish were treated, 6, 11, 16, 21, 26 or 31 days after the challenged infection, by elevating the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…It is widely documented that temperature has an effect on the rate of development of parasites, including microsporidial pathogens of fish (Olson 1981; Antonio & Hedrick 1995; Kim, Ogawa, Takahashi & Wakabayashi 1997). Temperature manipulation has therefore been advanced as a non‐pharmacological method of controlling microsporidian species like Glugea plecoglossi (Takahashi & Ogawa 1997). It has been used successfully for the control of L. salmonae in rainbow trout, Oncorhynchus mykiss (Walbaum), while still permitting the fish to develop immunity against this parasite (Speare, Beaman, Jones, Markham & Arsenault 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely documented that temperature has an effect on the rate of development of parasites, including microsporidial pathogens of fish (Olson 1981; Antonio & Hedrick 1995; Kim, Ogawa, Takahashi & Wakabayashi 1997). Temperature manipulation has therefore been advanced as a non‐pharmacological method of controlling microsporidian species like Glugea plecoglossi (Takahashi & Ogawa 1997). It has been used successfully for the control of L. salmonae in rainbow trout, Oncorhynchus mykiss (Walbaum), while still permitting the fish to develop immunity against this parasite (Speare, Beaman, Jones, Markham & Arsenault 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Although efficacy of the treatment depended largely on the developmental stage of the parasite present at the time of its usage (Takahashi and Ogawa, 1997), the treatment of cultured ayu with visible Glugea-cysts was quite effective (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that water temperature influences develop ment of fish microsporidians in the hosts; Microsporidium takedai in salmonid fish (Awakura, 1974), Glugea plecoglossi in ayu (Plecoglosus altivelis) (Takahashi and Egusa, 1977;Takahashi and Ogawa, 1997), Heterosporis (= Pleistophora) anguillarum in eel (Anguilla japonica) (Kanou and Fukui, 1982), and Enterocytozoon salmonis in chinook salmon (Oncorhynchus tshawytscha) (Anto nio and Hedrick, 1995 …”
Section: Discussionmentioning
confidence: 99%